On farm demonstration of faba bean (Vicia faba L.) varieties in orobanche infested areas of Ofla district, South Tigray, Ethiopia - Birhanu Amare; Tsehaye Birhane (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2020)
Faba bean variety demonstration was conducted at Adigollo kebelle (Ofla district, South Tigray, Ethiopia in 2016 main cropping season to demonstrate the performance of the Orobanche tolerant faba bean variety. The tested materials were improved (Hashenge) and local faba bean varieties. The demonstration was conducted in six farmers' field that has plot size of 20 m by 20 m. Farmers were selected based on their interest to share their plot of land Farmers' perception was collected individually and in group discussion form to evaluate the yield and yield components of the varieties at maturity stage. Moreover, grain yield and orobanche count per plot was measured from each plot. Based on the biological data, Hashenge variety gave higher grain yield (3.54 t/ha) as compared with the local variety (1.14 t/ha). Accordingly, Hashenge variety has shown 201.5% grain yield advantage over the local variety. On the other hand, orobanche count per plot was taken from each farmer's plot. In this regard, the population of orobanche weed grown in the plots of Hashenge variety was lower as compared to the local variety grown plots (27.36 and 43.52 plants per m2, respectively). This shows more resistance to orobanche weed was recorded in the improved variety (Hashenge). Based on farmers' perception, the Hashenge variety has better yield and other yield component performance as compared to the local variety and it was appreciated by farmers for further popularization and scaling up/out. Therefore, the improved and orobanche tolerant faba bean variety should be scaled out not only to the southern zone of Tigray region but also to other orobanche infested areas (locations) of the country, like south Wollo and North Gonder of the Amhara region, Ethiopia.